IMF-driven change to the Antarctic tropospheric temperature due to the global atmospheric electric circuit. (November 2018) - Lam, Mai Mai; Freeman, Mervyn P.; Chisham, Gareth
Abstract: We use National Centers for Environmental Prediction (NCEP)/National Center for Atmospheric Research (NCAR) reanalysis data to investigate the Antarctic mean tropospheric temperature anomaly associated with changes in the dawn-dusk component B y of the interplanetary magnetic field (IMF). We find that the mean tropospheric temperature anomaly for geographical latitudes ≤ −70° peaks at about 0.7 K and is statistically significant at the 5% level between air pressures of 1 000 and 500 hPa (∼0.1–5.6 km altitude above sea level) and for time lags with respect to the IMF of up to 7 days. The peak values of the air temperature anomaly occur at a greater time lag at 500 hPa (∼5.6 km) than at 1 000 - 600 hPa (∼0.1–4.2 km), which may indicate that the signature propagates vertically. The characteristics of prompt response and possible vertical propagation within the troposphere have previously been seen in the correlation between the IMF and high-latitude air pressure anomalies, known as the Mansurov effect, at higher statistical significances (1%). For time lags between the IMF and the troposphere of 0–6 days and altitudes between 1 000 and 700 hPa (∼0.1–3 km), the relationship between highly statistically significant (1% level) geopotential height anomaly values and the corresponding air temperature anomaly values is consistent with the standard lapse rate in atmospheric temperature. We conclude that we have identified the temperature signature of the Mansurov effect in the Antarctic troposphere. Since these tropospheric anomalies have been associated with B y -driven anomalies in the electric potential of the ionosphere, we further conclude that they are caused by IMF-induced changes to the global atmospheric electric circuit (GEC). Our results support the view that variations in the ionospheric potential act on the troposphere, possibly via the action of consequent variations in the downwards current of the GEC on tropospheric clouds. Highlights: Antarctic air temperature is influenced by the interplanetary magnetic field. The effect exists between about 0–5.6 km above sea level with a 27-day periodicity. Like the air pressure effect, peak amplitude (0.7 K) is for a time lag of just days. There is evidence of vertical propagation of the signal from the lower troposphere. Results indicate a mechanism involving the global atmospheric electric circuit.